A papermaking process for cultural paper
Patent Information
- Application Number
- CN202610711321.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-22
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-05-22
AI Technical Summary
[0005]但发明人在研究中发现,上述技术方案虽通过多孔硅酸钙的微观多孔结构和低密度特性,提高了松厚度,但这种疏松多孔的内部结构也使得纸张表面结合力变差,使得层间结合强度降低,在印刷或高速书写等外力作用下,纸张表面的纤维及填料颗粒容易发生剥离、脱落,引发较为严重的掉毛掉粉现象,直接影响纸张的使用效果与外观完整性
1.通过采用针叶木浆的长纤维提供物理强度支撑,利用机械浆保证高松厚度,通过壳聚糖接枝丙烯酰胺-马来酸酐共聚物的桥接与缠绕作用,增强了纤维间及纤维-填料间的结合力,提升结合强度,从而在实现高灰分和高松厚度的同时,抑制了纸张的脱粉与掉毛现象,确保了纸张表面的完整性与印刷性。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of papermaking technology, specifically relating to a papermaking process for cultural paper. Background Technology
[0002] Cultural paper, as an important medium for information recording and dissemination, is widely used in writing, printing, and office applications. Its quality directly affects writing smoothness, printability, appearance, and durability. With the continuous development of the paper industry, the market has placed higher demands on the comprehensive performance of cultural paper. Adding fillers to the pulp system during the paper production process is a common technique to improve paper whiteness, opacity, and smoothness while reducing production costs.
[0003] However, as the amount of filler added increases, due to the lack of binding ability of the filler particles themselves, the addition of a large amount of filler will occupy the binding sites between fibers, hindering the formation and bonding of hydrogen bonds between fibers, which in turn leads to a decrease in the physical strength of the paper. In particular, the bulk of the paper will decrease significantly with the increase of ash content, making the paper thinner, harder and stiffer, and worse in feel.
[0004] To address the aforementioned technical problems, Chinese invention patent application CN118581764A, published on September 3, 2024, proposes a method for preparing cultural paper. This technical solution involves adding porous calcium silicate, or a mixture of porous calcium silicate and calcium carbonate, during the paper preparation process. While maintaining a high ash content, the porous structure of the filler supports the paper thickness, thereby solving the problem of low bulk and thickness in high-ash cultural paper.
[0005] However, the inventors discovered in their research that although the above-mentioned technical solution improves the bulk through the microporous structure and low density characteristics of porous calcium silicate, this loose and porous internal structure also makes the paper surface bonding force worse and reduces the interlayer bonding strength. Under the action of external forces such as printing or high-speed writing, the fibers and filler particles on the paper surface are prone to peeling and falling off, causing serious lint and dusting, which directly affects the paper's performance and appearance integrity. Summary of the Invention
[0006] To improve the bonding strength of cultural paper, this invention provides a papermaking process for cultural paper.
[0007] This invention provides a papermaking process for cultural paper, employing the following technical solution: A papermaking process for cultural paper includes the following steps: Initial pulp preparation: Bleached sulfate softwood pulp and poplar mechanical pulp are pulped separately and then mixed evenly to obtain the initial pulp; the initial pulp, by composition and mass parts, includes 10-15 parts of bleached sulfate softwood pulp and 85-90 parts of poplar mechanical pulp. Slurry treatment: Add wet-end additives to the initial slurry, mix evenly to obtain papermaking slurry; the wet-end additives, based on the mass parts of the initial slurry, include 0.3-0.6 parts of chitosan-grafted acrylamide-maleic anhydride copolymer, 0.8-1.2 parts of polyaluminum chloride, 16-20 parts of calcium carbonate, and 0.09-0.15 parts of cationic polyacrylamide; The grafting rate of the chitosan-grafted acrylamide-maleic anhydride copolymer was 58–72 wt%. Papermaking and post-processing: The papermaking pulp is diluted with process water, and then processed by wire forming, pressing and dewatering, and drying to produce cultural paper.
[0008] By adopting the above technical solutions, from a fiber perspective, bleached sulfate softwood pulp fibers are long and thin with strong interweaving ability, forming a solid fiber network skeleton, while poplar mechanical pulp fibers are short, coarse, and porous. This reduces production costs while providing good bulk for the paper. After pulping, the two are mixed, and the long fibers of the softwood pulp fill the gaps between the poplar mechanical pulp fibers, increasing the bonding sites between fibers and reducing dusting and linting caused by fiber slippage. Chitosan-grafted acrylamide-maleic anhydride copolymer has cationic and hydrophilic properties, adsorbing onto the fiber surface, enhancing the hydrogen bonding and chemical bonding between fibers, and strengthening the interlayer bonding force. At the same time, it can disperse calcium carbonate filler, avoiding the decrease in bonding force caused by filler agglomeration. Polyaluminum chloride promotes the coagulation of fibers and fillers, reducing filler loss during papermaking. Cationic polyacrylamide strengthens the bonding between fibers and between fibers and fillers, improving the density of the paper structure. Calcium carbonate filler, under the dispersion effect of additives, is evenly distributed in the fiber network, meeting the high ash content requirements while ensuring paper bulk.
[0009] Specifically, the chitosan-grafted acrylamide-maleic anhydride copolymer molecular chain is rich in amino and carboxyl groups, which not only has strong cationic properties and can be effectively adsorbed on the surface of negatively charged fibers and fillers, but its long side chains with high grafting rate can also form physical entanglement and bridging between fibers, greatly enhancing the bonding strength between fibers and between fibers and fillers, thereby inhibiting the phenomenon of powder and lint shedding.
[0010] Optionally, the initial pulp further includes 15 to 25 parts of fine fiber waste pulp, and the mass fraction of the poplar mechanical pulp is adjusted to 60 to 75 parts; The method for preparing the fine fiber waste pulp is as follows: Select waste paper of the same type for cultural use, break it down in a hydrapulper, and then perform high-consistency pulping treatment to control the degree of beating at 45-60°SR. Then, purify it through an 80-mesh arc screen to obtain fine fiber waste pulp with a concentration of 10-15wt%.
[0011] By adopting the above technical solution, the fine fiber pulp undergoes high-consistency beating, resulting in displacement, deformation, and even breakage of the fiber cell walls. This produces a large amount of water absorption, swelling, and fine fiberization. These fine fibers with high specific surface area can fill the gaps between the long fibers of coniferous wood and the mechanical pulp fibers of poplar wood during the paper forming process, acting as micro-fillers and binders. This not only increases the contact area between fibers and the number of hydrogen bonds, further improving the surface strength and density of the paper, but also realizes the high-value recycling of waste and reduces production costs.
[0012] Optionally, before disintegration at a temperature of 25–35°C, a fiber interface activating component, accounting for 0.2–0.4 wt% of the mass of waste paper of the same type of cultural paper, is added; the fiber interface activating component includes sorbitol, glycerol, and quaternized chitosan oligosaccharide, wherein the mass ratio of sorbitol, glycerol, and quaternized chitosan oligosaccharide is 1.5–3.5:0.8–1.5:1.
[0013] By adopting the above technical solutions, the strong hydrophilicity of sorbitol and glycerol can penetrate into the fiber cell wall, promote fiber water absorption and swelling, reduce fiber rigidity, and facilitate high-consistency pulping. Quaternized chitosan oligosaccharide not only carries a positive charge, which can neutralize the negative charge of the fiber, but more importantly, the quaternary ammonium groups on its molecular chain can form hydrogen bonds or electrostatic adsorption with the hydroxyl groups on the fiber surface, playing an anchoring role. Through the combined action of the three substances, the surface activity of the paper fiber is improved, making it easier for the fiber to achieve fibrillation during the pulping process, thereby obtaining a higher degree of freeness with lower energy consumption, and giving the fine fiber paper pulp a better binding ability.
[0014] Optionally, the degree of substitution of the quaternary ammonium group in the quaternized chitosan oligosaccharide is 0.1 to 0.5.
[0015] If the substitution is too low, the positive charge density on the molecular chain is insufficient and cannot be effectively adsorbed on the negatively charged fiber surface, resulting in poor activation effect. If the substitution is too high, the water solubility of quaternized chitosan oligosaccharide decreases and it is easy to agglomerate. Not only will it fail to play an activation role, but it will also cause fiber network blockage, damage the bulk of the paper, and may also affect the dispersibility of filler, resulting in high ash content not meeting the standard.
[0016] Setting the degree of substitution within this range ensures sufficient cationic charge density for strong adsorption while maintaining the flexibility and hydrophilicity of the molecular chains. This allows the fibers to bind firmly to the fiber surface and effectively promote hydration within the fibers, thereby maximizing the activation effect at the fiber interface and ensuring a highly active state for the pulp fibers.
[0017] Optionally, in the slurry treatment step, the wet-end additive further includes sodium lignosulfonate-modified bentonite, wherein the amount of sodium lignosulfonate-modified bentonite added is 1.5 to 2.5 wt% of the mass of calcium carbonate; The preparation steps of the sodium lignosulfonate modified bentonite are as follows: Calcium-based bentonite is sieved through an 80-mesh sieve, and 3-5 wt% sodium lignosulfonate is added to the bentonite. Water is added and stirred to obtain a uniform slurry with a solid content of 15-20 wt%.
[0018] By adopting the above technical solution, sodium lignosulfonate is used to modify bentonite, which not only expands the interlayer spacing of bentonite and enhances its specific surface area and adsorption capacity, but also gives the bentonite surface a negative charge and steric hindrance effect. In the paper forming process, this modified bentonite can form a denser "micro-floc network" with cationic polyacrylamide, capturing and fixing fine fibers and calcium carbonate particles, preventing them from being lost during the dehydration process of the wire section. This improves the uniformity and density of the paper's internal structure, further reduces surface porosity and strength weaknesses caused by the loss of fine components, and further improves the overall surface strength and printability of the paper.
[0019] Optionally, in the slurry treatment step, the wet-end additives are added in the following order: add polyaluminum chloride to the initial slurry, stir and disperse for 3-5 minutes, then add calcium carbonate, stir and disperse for 5-7 minutes, then add chitosan-grafted acrylamide-maleic anhydride copolymer, ultrasonically disperse for 4-6 minutes, then add cationic polyacrylamide, stir for 2-4 minutes, and finally add sodium lignosulfonate-modified bentonite, stir and disperse until uniformly mixed.
[0020] By adopting the above technical solution, polyaluminum chloride (PAC) is first added to neutralize the charge of the fiber, which facilitates the adsorption of subsequent fillers. Then, calcium carbonate is added to initially retain the fiber on the PAC-modified fiber surface. Next, chitosan-grafted acrylamide-maleic anhydride copolymer is added and ultrasonically dispersed to allow it to fully extend, encapsulate and bridge the fiber and filler. Then, cationic polyacrylamide (CPAM) is added to form a macro-flocculated network. Finally, sodium lignosulfonate-modified bentonite is added to form a micro-flocculated structure with CPAM, further achieving retention. Therefore, a higher filler retention rate and fiber bonding strength are obtained.
[0021] Optionally, in the papermaking and post-processing steps, the process water includes treated papermaking white water and tap water, wherein the volume ratio of treated papermaking white water to tap water is 0.8 to 1.2:1; the treatment step of the papermaking white water includes: sedimenting and separating the white water generated during papermaking to obtain upper overflow clarified water, wherein 60 to 80 wt% of the upper overflow clarified water is used for pulp dilution, and 20 to 40 wt% of the overflow clarified water is discharged after environmental protection treatment.
[0022] By adopting the above technical solution, the upper overflow clarified water is reused for pulp dilution, which not only saves water resources but also retains some beneficial solubilizing agents and fine fibers, replenishes fiber binding sites, promotes fiber interweaving, and improves bonding strength. At the same time, the reused white water can maintain a reasonable pulp concentration and viscosity, which is beneficial for fiber formation and bulk control. In addition, the discharge of some overflow clarified water after environmental treatment plays a role in controlling the concentration of anionic impurities and organic acids in the system, thereby maintaining the stability of the wet end chemical environment and thus maintaining process stability and paper quality.
[0023] Optionally, in the papermaking and post-processing steps, the precipitation separation is performed as follows: Pretreatment: The white water generated from papermaking is first passed into an inclined plate sedimentation tank, and flocculant accounting for 0.06-0.1 wt% of the white water mass is added. The mixture is stirred at 80-120 r / min for 5-8 min. The flocculant includes polyferric sulfate and diatomaceous earth, wherein the mass ratio of polyferric sulfate to diatomaceous earth is 1-3:1. Filtration: The pretreated white water is filtered through a filter cloth with a pore size of 2-5 μm to obtain filtered white water; Impurity removal: Quaternized polyamide and polyoxyethylene polyoxypropylene ether are added to the filtered white water, wherein the amount of quaternized polyamide and polyoxyethylene polyoxypropylene ether added accounts for 0.03-0.06 wt% and 0.02-0.04 wt% of the mass of the filtered white water, respectively.
[0024] By adopting the above technical solution, firstly, efficient flocculation is carried out in an inclined plate sedimentation tank using polyferric sulfate and diatomaceous earth as flocculants, removing most of the suspended solids through charge neutralization and net sweeping action; secondly, physical filtration is performed through filter cloth to trap the remaining fine fibers and fillers, preventing them from entering the recycled white water; finally, quaternized polyamide and polyoxyethylene polyoxypropylene ether are added to the filtered white water. Quaternized polyamide can further adsorb and remove anionic waste in the water, while polyoxyethylene polyoxypropylene ether can effectively reduce the surface tension of the water, promote impurity separation, prevent foam generation, and remove oily impurities. This deep purification treatment ensures the high cleanliness of the recycled water, avoids impurities occupying the active sites on the fiber surface, and thus guarantees the bonding strength of the paper.
[0025] Optionally, in the papermaking and post-processing steps, the drying method is as follows: first, dry at 80-90℃ for 10-15 minutes; then dry at 110-120℃ for 8-10 minutes; and finally dry at 95-105℃ for 5-8 minutes.
[0026] By adopting the above technical solution, the paper is first gently pre-dried at 80-90℃ to preliminarily dehydrate and shape the paper, avoiding premature surface sealing and the formation of a hard shell due to high-temperature rapid drying. Then, it is rapidly dried at 110-120℃ to efficiently remove internal moisture, promote the formation and stabilization of hydrogen bonds between fibers, and strengthen the bonding strength. Finally, it is cooled and dried at 95-105℃. This drying method helps to control the vapor pressure inside the paper and prevent the damage to the fiber network structure caused by violent evaporation of moisture. In addition, the appropriate cooling and drying stage is conducive to the relaxation of fiber and auxiliary molecules, reducing drying stress and avoiding micro-cracks on the paper surface due to excessive shrinkage, thereby maintaining the flexibility and bonding strength of the paper surface.
[0027] Optionally, in the papermaking and post-processing steps, an equilibration step is set after the drying process. The equilibration step is as follows: first, the paper is naturally cooled to below 40°C, and then, under the conditions of 25-28°C and 45-55% relative humidity, it is allowed to stand for equilibration for 12-15 minutes.
[0028] By adopting the above technical solution, the paper, after being dried, has a high temperature and low moisture content, and the internal fibers are in a state of tension. By first naturally cooling it to below 40°C to eliminate thermal stress, and then allowing it to stand in a constant temperature and humidity environment for equilibrium, the moisture inside the paper is redistributed and adsorbed, reaching a state of rehydration in equilibrium with the environment. This redistribution of moisture helps the fibers to further swell and rebuild hydrogen bonds, making the physical structure of the paper more stable. After the equilibrium treatment, the surface smoothness and surface strength of the paper are further improved, preventing dusting and linting caused by environmental changes during subsequent printing or handling, and ensuring the consistency of product quality.
[0029] In summary, the present invention has at least one of the following beneficial technical effects: 1. By using long fibers from softwood pulp to provide physical strength support, and mechanical pulp to ensure high bulk, the bonding force between fibers and between fibers and fillers is enhanced through the bridging and entanglement effect of chitosan grafted with acrylamide-maleic anhydride copolymer, thereby improving the bonding strength. Thus, while achieving high ash content and high bulk, paper dusting and linting are suppressed, ensuring the integrity of the paper surface and printability.
[0030] 2. By utilizing the swelling effect of polyols and the anchoring effect of quaternary ammonium groups, the surface activity and beating efficiency of waste paper fibers are improved, enabling them to achieve fiberization with lower energy consumption. At the same time, this highly active fine fiber waste paper pulp acts as a micro-binder in the paper sheet, increasing the contact area and the number of hydrogen bonds between fibers. This not only solves the problem of fiber resource recycling but also strengthens the internal bonding strength of the paper from a microstructural perspective.
[0031] 3. By adopting a feeding sequence, the synergistic effect of additives is maximized; the three-stage treatment process of flocculation, filtration and impurity removal used in papermaking white water removes anionic waste and colloidal substances from the system, preventing impurities from occupying fiber binding sites and consuming cationic additives, ensuring the efficient retention of fillers and fine fibers, thereby maintaining the long-term stability of paper physical properties and establishing a stable chemical environment in the papermaking wet end.
[0032] 4. By adopting segmented drying, the damage to the fiber network structure and the formation of a hard shell on the surface are prevented; the balancing treatment eliminates the internal drying stress, while promoting further fiber swelling and hydrogen bond reconstruction, effectively reducing the generation of surface microcracks, and further solving the problem of surface strength reduction caused by stress concentration during the drying process. Detailed Implementation
[0033] Unless otherwise specified, the experimental methods used in the embodiments of this application are all conventional methods, and the materials used are all commercially available unless otherwise specified. The materials used in the embodiments of this invention are all industrial grade.
[0034] The present invention will be further described in detail below with reference to the embodiments.
[0035] Example 1: This example discloses a papermaking process for cultural paper.
[0036] A papermaking process for cultural paper, the specific steps of which are as follows: (1) Initial pulp preparation: Bleached sulfate softwood pulp and poplar mechanical pulp were beaten separately. The bleached sulfate softwood pulp was beaten to 48°SR and the poplar mechanical pulp was beaten to 32°SR. By mass, 10 parts of the beaten bleached sulfate softwood pulp and 90 parts of the beaten poplar mechanical pulp were placed in a mixing tank and stirred for 15 minutes at 28°C and 100 r / min until homogeneous to obtain the initial pulp. The concentration of the initial pulp was 12 wt%. (2) Slurry treatment: Add wet-end additives to the initial slurry obtained above. The wet-end additives are added in the following amounts based on the mass of the initial slurry: 0.3 parts of chitosan-grafted acrylamide-maleic anhydride copolymer, 0.8 parts of polyaluminum chloride, 16 parts of calcium carbonate, and 0.09 parts of cationic polyacrylamide; wherein the grafting rate of chitosan-grafted acrylamide-maleic anhydride copolymer is 65%. In this embodiment, the order of adding wet-end additives is as follows: add polyaluminum chloride to the initial slurry, stir and disperse at 125 r / min for 4 min, then add calcium carbonate, stir and disperse at 125 r / min for 6 min, then add chitosan-grafted acrylamide-maleic anhydride copolymer, ultrasonically disperse at 300 W and 20 kHz for 5 min, then add cationic polyacrylamide, stir at 125 r / min for 3 min until the mixture is uniform. The wet-end additives and initial slurry were mixed evenly and stirred at 28°C and 120 r / min for 20 min. After being mixed evenly, the papermaking slurry was prepared, and the concentration of the papermaking slurry was adjusted to 8 wt%. (3) Papermaking and post-processing: Tap water is used as process water to dilute the papermaking pulp to a pulp concentration of 1.2wt%. The diluted papermaking pulp is sent to the wire section, and the wire section speed is controlled at 280m / min for forming to obtain wet paper sheets. The wet paper sheets are sent to the press section, and a three-roll press is used to control the press pressure at 0.3MPa and the press time at 30s for dewatering, so that the moisture content of the wet paper sheets is reduced to 45%. Then, the paper is dried. The drying method is as follows: first, dry at 85℃ for 12min, then dry at 115℃ for 9min, and finally dry at 100℃ for 6min. After drying, the moisture content of the paper sheets is 6%, and cultural paper is obtained.
[0037] The preparation method of chitosan-grafted acrylamide-maleic anhydride copolymer is as follows: a. Chitosan pretreatment: Take 10 parts of chitosan, add 1000 parts of deionized water, and then add glacial acetic acid to adjust the pH of the system to 5.0. Stir at 35℃ and 150r / min for 30min until the chitosan is completely dissolved to obtain a chitosan aqueous solution. b. Graft polymerization reaction: The chitosan aqueous solution obtained above was heated to 55°C, and 35 parts of acrylamide and 12 parts of maleic anhydride were added sequentially. The mixture was stirred for 15 min to completely dissolve the monomer. Then, 0.8 parts of potassium persulfate-sodium bisulfite mixture were added. The mass ratio of potassium persulfate to sodium bisulfite was 2:1. The reaction temperature was controlled at 55°C and the stirring speed was 180 r / min. The reaction was carried out at a constant temperature for 4.5 h to obtain the graft polymerization reaction solution. c. Purification and drying: Add anhydrous ethanol to the graft polymerization reaction solution, the amount of which is twice the volume of the reaction solution. After stirring evenly, let it stand for 30 minutes to allow the copolymer to fully precipitate. Filter and collect the precipitate, wash it three times with anhydrous ethanol to remove unreacted monomers and impurities. Place the washed precipitate in a vacuum drying oven and dry it for 2.5 hours at 65°C and a vacuum degree of 0.08 MPa. After pulverizing, pass it through an 80-mesh sieve to obtain a chitosan-grafted acrylamide-maleic anhydride copolymer with a grafting rate of 65 wt%.
[0038] In this embodiment, ① the bleached sulfate softwood pulp is Yunnan three-needle softwood pulp; ② the poplar mechanical pulp is commercially available bleached poplar chemimechanical pulp with a whiteness of 75%; ③ the calcium carbonate is light calcium carbonate with a mesh size of 2000; ④ the cationic polyacrylamide has a molecular weight of 8 million and an ionicity of 30%.
[0039] The main tests include surface strength, interlayer bond strength, bulk, ash content, folding endurance, and whiteness.
[0040] (1) Surface strength (m / s): reflects the paper’s ability to resist lint, dust, and surface peeling. The higher the test value, the less lint and dust will be generated during printing or writing. The test is conducted in accordance with GB / T 2679.16-2021 (IGT method). (2) Interlayer bond strength (N / 15mm): Reflects the paper’s resistance to delamination in the Z-direction, i.e., the thickness direction. The higher the test value, the stronger the resistance to delamination. The test is conducted in accordance with GB / T 31110-2014 (Z-direction tensile strength). (3) Looseness (cm) 3 / g): Reflects the bulkiness and thickness of cultural paper. The higher the bulk, the more fluffy, thick, and soft the paper is, and it is not stiff or hard. The lower the bulk, the more compact, thin, stiff, and poor the paper is. The test is based on GB / T 451.3-2002 (thickness). After measuring the thickness, it is calculated in combination with the basis weight. (4) Ash content (wt%): reflects the retention rate and addition of filler in the paper, and verifies the balance between strength and bulk under high ash content. Under the premise that the strength meets the requirements, the higher the ash content, the more economic and performance advantages it has; the test is conducted in accordance with GB / T 742-2018. (5) Folding endurance (times): Reflects the paper’s flexibility and durability under repeated bending. The higher the folding endurance, the tighter the fiber bond, the stronger the flexibility, the smaller the internal drying stress, and the fewer the surface microcracks. The test is conducted in accordance with GB / T 455-2002 (MIT method). (6) Whiteness (%): Reflects the appearance index of cultural paper; the test is conducted in accordance with GB / T 8940.2-2002.
[0041] Example 2: This example discloses a papermaking process for cultural paper.
[0042] In this embodiment: (1) Initial pulp preparation: Bleached sulfate softwood pulp and poplar mechanical pulp were beaten separately. The bleached sulfate softwood pulp was beaten to 48°SR and the poplar mechanical pulp was beaten to 32°SR. By mass, 15 parts of the beaten bleached sulfate softwood pulp and 85 parts of the beaten poplar mechanical pulp were placed in a mixing tank and stirred for 15 minutes at 28°C and 100 r / min until homogeneous to obtain the initial pulp. The concentration of the initial pulp was 12 wt%. (2) Slurry treatment: Add wet-end additives to the initial slurry obtained above. The wet-end additives are added in the following amounts according to the mass of the initial slurry: 0.6 parts of chitosan-grafted acrylamide-maleic anhydride copolymer, 1.2 parts of polyaluminum chloride, 20 parts of calcium carbonate, and 0.15 parts of cationic polyacrylamide; wherein the grafting rate of chitosan-grafted acrylamide-maleic anhydride copolymer is 65%. The order of addition of each component of the wet-end additive is the same as in Example 1; Everything else is exactly the same as in Example 1.
[0043] Example 3: This example discloses a papermaking process for cultural paper.
[0044] In this embodiment: (1) Initial pulp preparation: Bleached sulfate softwood pulp and poplar mechanical pulp were beaten separately. The bleached sulfate softwood pulp was beaten to 48°SR and the poplar mechanical pulp was beaten to 32°SR. By mass, 12 parts of the beaten bleached sulfate softwood pulp and 88 parts of the beaten poplar mechanical pulp were placed in a mixing tank and stirred for 15 minutes at 28°C and 100 r / min until homogeneous to obtain the initial pulp. The concentration of the initial pulp was 12 wt%. (2) Slurry treatment: Add wet-end additives to the initial slurry obtained above. The wet-end additives are added in the following amounts according to the mass of the initial slurry: 0.45 parts of chitosan-grafted acrylamide-maleic anhydride copolymer, 1.0 part of polyaluminum chloride, 18 parts of calcium carbonate, and 0.12 parts of cationic polyacrylamide; wherein the grafting rate of chitosan-grafted acrylamide-maleic anhydride copolymer is 65%. The order of addition of each component of the wet-end additive is the same as in Example 1; Everything else is exactly the same as in Example 1.
[0045] The cultural paper prepared in Examples 1-3 was tested, and the test results are shown in Table 1: Table 1 Test data of cultural paper in Examples 1-3 Surface strength (m / s) 2.45 2.68 2.58 Interlayer bond strength (N / 15mm) 145 158 152 <![CDATA[Bulk (cm 3 / g)]]> 1.90 1.84 1.88 Ash content (wt%) 22.5 22.8 23.1 Flexural endurance (times) 186 203 198 Whiteness (%) 88.8 88.5 88.6 By comparing Examples 1-3, it can be seen that Example 1, with its low proportion of softwood pulp, achieved the highest bulk and whiteness. This is because the fewer long fibers resulted in a relatively loose fiber network structure, and softwood pulp is generally slightly darker in color than bleached poplar pulp, thus its optical properties and bulkiness were optimal. However, its surface strength and folding endurance were the lowest among the three examples. Example 2 increased the proportion of softwood pulp, enhancing the interwoven network between fibers, resulting in the highest surface strength and folding endurance among the three examples. However, the dense fiber arrangement led to a decrease in bulk. Example 3 balanced the proportion of long and short fibers, achieving the highest ash retention rate, and all indicators remained at a high level. Overall, all three examples maintained the stability of the paper structure and the retention of fillers.
[0046] Example 4: This example discloses a papermaking process for cultural paper.
[0047] In this embodiment, the initial pulp also includes 20 parts of fine fiber waste pulp, specifically: (1) Initial pulp preparation: Bleached sulfate softwood pulp and poplar mechanical pulp were beaten separately. The bleached sulfate softwood pulp was beaten to 48°SR and the poplar mechanical pulp was beaten to 32°SR. By mass, 12 parts of beaten bleached sulfate softwood pulp, 68 parts of beaten poplar mechanical pulp and 20 parts of fine fiber waste pulp were placed in a mixing tank and stirred for 15 minutes at 28°C and 100r / min until they were mixed evenly to obtain the initial pulp. The concentration of the initial pulp was 12wt%.
[0048] The preparation method of fine fiber waste pulp is as follows: Select waste paper of the same type for cultural use (brightness 78%), and break it down to ≤5cm in a hydrapulper at a liquid-to-solid ratio of 10:1, 28℃, and 1500r / min for 30min. Then, perform high-consistency pulping treatment to obtain a concentration of 15wt% and a freeness of 52°SR. Finally, purify it through an 80-mesh arc screen to obtain fine fiber waste pulp with a concentration of 12wt%. In this embodiment, the waste paper for cultural paper refers to waste paper and scraps from the production process of cultural paper; everything else is exactly the same as in Embodiment 3.
[0049] Example 5: This example discloses a papermaking process for cultural paper.
[0050] The difference between this and Example 4 is that, in the preparation method of the fine fiber waste pulp: before disintegration at a temperature of 28°C, a fiber interface activating component accounting for 0.3 wt% of the mass of similar cultural paper waste is added; the fiber interface activating component is sorbitol, glycerol, and quaternized chitosan oligosaccharide, wherein the mass ratio of sorbitol, glycerol, and quaternized chitosan oligosaccharide is 2.5:1.2:1, and the degree of substitution of the quaternary ammonium group of the quaternized chitosan oligosaccharide is 0.3; Everything else is exactly the same as in Example 4.
[0051] Example 6: This example discloses a papermaking process for cultural paper.
[0052] The difference between this and Example 5 is that, in the slurry treatment step, the wet-end additive further includes sodium lignosulfonate modified bentonite, and the amount of sodium lignosulfonate modified bentonite added accounts for 2.0 wt% of the mass of calcium carbonate; In this embodiment, the order of adding wet-end additives is as follows: add polyaluminum chloride to the initial slurry, stir and disperse at 125 r / min for 4 min, then add calcium carbonate, stir and disperse at 125 r / min for 6 min, then add chitosan-grafted acrylamide-maleic anhydride copolymer, ultrasonically disperse at 300 W and 20 kHz for 5 min, then add cationic polyacrylamide, stir at 125 r / min for 3 min, and finally add sodium lignosulfonate modified bentonite, stir and disperse at 125 r / min for 5 min until the mixture is uniform. The preparation steps of sodium lignosulfonate modified bentonite are as follows: Take 100 parts of bentonite and sieve it through an 80-mesh sieve. Add 4 parts of sodium lignosulfonate and add water. Stir at 30℃ and 200r / min for 60min. Add water to adjust the solid content to 18wt% to obtain sodium lignosulfonate modified bentonite slurry. Everything else is exactly the same as in Example 5.
[0053] Example 7: This example discloses a papermaking process for cultural paper.
[0054] The difference between this and Example 6 is that, in the papermaking and post-processing steps, the process water used is treated papermaking white water and tap water, wherein the volume ratio of treated papermaking white water to tap water is 1:1. The treatment steps for the papermaking white water are as follows: the white water generated during papermaking is separated by sedimentation to obtain the upper overflow clarified water, of which 70wt% of the upper overflow clarified water is used for pulp dilution, and 30% of the overflow clarified water is discharged after environmental treatment; The precipitation treatment method is as follows: a. Pretreatment: The white water generated by papermaking, with a concentration of 0.8 wt%, is first passed into an inclined plate sedimentation tank, and flocculant accounting for 0.08 wt% of the white water mass is added. The mixture is stirred at 100 r / min for 6 min. The flocculant includes polyferric sulfate and diatomaceous earth, wherein the mass ratio of polyferric sulfate to diatomaceous earth is 2:1. b. Filtration: The pretreated white water is filtered through a filter cloth with a pore size of 3μm to obtain filtered white water with a concentration of ≤0.1wt%; c. Impurity removal: Add quaternized polyamide and polyoxyethylene polyoxypropylene ether to the filtered white water, wherein the amount of quaternized polyamide and polyoxyethylene polyoxypropylene ether added accounts for 0.045 wt% and 0.03 wt% of the mass of the filtered white water, respectively. Stir at 100 r / min for 10 min, and let stand for 15 min after stirring. Everything else is exactly the same as in Example 6.
[0055] Example 8: This example discloses a papermaking process for cultural paper.
[0056] The difference between this and Example 7 is that, in the papermaking and post-processing steps, an equilibration step is added after the drying process. The equilibration step is as follows: first, it is naturally cooled to 35°C, and then it is allowed to stand for equilibration for 12 minutes at a temperature of 26±1°C and a relative humidity of 50±1%. Everything else is exactly the same as Example 7.
[0057] The cultural paper prepared in Examples 4-8 was tested, and the test results are shown in Table 2: Table 2 Test data for cultural paper in Examples 4-8 Surface strength (m / s) 2.72 2.85 2.98 3.05 3.15 Interlayer bond strength (N / 15mm) 160 168 175 180 185 <![CDATA[Bulk (cm 3 / g)]]> 1.90 1.91 1.93 1.93 1.95 Ash content (wt%) 23.0 23.2 23.5 23.8 24.1 Flexural endurance (times) 215 232 248 250 265 Whiteness (%) 88.2 88.0 87.7 87.5 87.5 By comparing Example 4 with Example 3, it can be seen that the addition of fine fiber pulp in Example 4 improves all strength indicators, while slightly increasing bulk. The pulp contains a large number of fine fibers that have been beaten and highly fibrillated. These fine fibers can fill the large pores of the native fiber network, increasing the contact area and hydrogen bond sites between fibers. This effect not only enhances the internal bonding force of the paper and improves its strength and folding endurance, but also prevents excessive fiber collapse due to the supporting effect of the fine fibers, thereby slightly increasing the bulk of the paper while improving strength.
[0058] By comparing Example 5 with Example 4, it can be seen that Example 5 adds a fiber interface activating component. This activating component contains chemical substances that can swell the fiber, remove surface impurities, or increase surface charge. It activates the fiber surface, making it easier to absorb water and swell, and expose more hydroxyl groups, thereby enhancing the hydrogen bonding force between fibers. This enhanced bonding force improves folding endurance and interlayer bonding strength. However, the activating component may slightly change the optical refractive index of the fiber or introduce trace amounts of colored groups, resulting in a slight decrease in whiteness.
[0059] By comparing Example 6 with Example 5, it can be seen that after adding sodium lignosulfonate modified bentonite in Example 6, the ash content, surface strength, and bulk increased. Modified bentonite has a unique layered structure and a large specific surface area. Sodium lignosulfonate helps bentonite particles to be evenly dispersed and adsorbed on the fiber surface, forming a particle retention system, thereby improving the retention rate of filler (ash). The filler particles fill the gaps between fibers, which not only increases the bulk of the paper, but also further enhances the surface strength through physical interlocking. At the same time, the adsorption of sodium lignosulfonate modified bentonite may reduce the whiteness within an acceptable range.
[0060] Comparing Example 7 with Example 6, it can be seen that the addition of recycled white water to the process water in Example 7 improved ash content, folding endurance, and interlayer bonding strength, but reduced whiteness. The reason for this is that the white water is rich in dissolved solids, microfibers, and residual chemical additives from previous processes. These substances further fill the gaps in the fiber network and enhance the bonding, thereby improving folding endurance and ash retention. However, the recycling of white water also leads to the accumulation of anionic waste and trace amounts of colored substances in the system. These impurities are adsorbed on the surface of fibers and fillers, resulting in a decrease in the overall whiteness of the paper.
[0061] By comparing Example 8 with Example 7, it can be seen that the overall performance indicators of Example 8 are relatively better. Shrinkage stress is easily generated during the paper drying process, which leads to microcracks at the fiber bonding points. The balance treatment eliminates the residual stress inside the paper. By controlling the drying gradient and moisture distribution, the fiber network is cured under low stress, which not only releases the bonding potential of the fibers, but also avoids the generation of microcracks. Thus, while further improving the bulk, the physical strength is maximized.
[0062] Comparative Example 1: This comparative example discloses a papermaking process for cultural paper.
[0063] The difference between this comparative example and Example 3 lies in the different mass fractions of the initial slurry, specifically: Initial pulp preparation: Bleached sulfate softwood pulp and poplar mechanical pulp were beaten separately. The bleached sulfate softwood pulp was beaten to 48°SR and the poplar mechanical pulp was beaten to 32°SR. By mass, 8 parts of the beaten bleached sulfate softwood pulp and 92 parts of the beaten poplar mechanical pulp were placed in a mixing tank and stirred for 15 minutes at 28°C and 100 r / min until homogeneous to obtain the initial pulp with a concentration of 12 wt%. All other aspects were exactly the same as in Example 3.
[0064] Comparative Example 2: This comparative example discloses a papermaking process for cultural paper.
[0065] In this comparative example, the difference from Example 3 is that the mass fraction of chitosan-grafted acrylamide-maleic anhydride copolymer in the wet end additive is 0.2 parts, while the grafting rate remains unchanged; otherwise, it is exactly the same as Example 3.
[0066] Comparative Example 3: This comparative example discloses a papermaking process for cultural paper.
[0067] In this comparative example, the difference from Example 3 is that the mass fraction of chitosan-grafted acrylamide-maleic anhydride copolymer added to the wet-end additive remains unchanged, but the grafting rate of the chitosan-grafted acrylamide-maleic anhydride copolymer is 50 wt%. The preparation method of chitosan-grafted acrylamide-maleic anhydride copolymer is as follows: a. Chitosan pretreatment: Take 10 parts of chitosan, add 1000 parts of deionized water, and then add glacial acetic acid to adjust the pH of the system to 5.0. Stir at 35℃ and 150r / min for 30min until the chitosan is completely dissolved to obtain a chitosan aqueous solution. b. Graft polymerization reaction: The chitosan aqueous solution obtained above was heated to 55°C, and 25 parts of acrylamide and 8 parts of maleic anhydride were added sequentially. The mixture was stirred for 15 min to completely dissolve the monomer. Then, 0.8 parts of potassium persulfate-sodium bisulfite mixture were added. The mass ratio of potassium persulfate to sodium bisulfite was 2:1. The reaction temperature was controlled at 55°C and the stirring speed was 180 r / min. The reaction was carried out at a constant temperature for 4.5 h to obtain the graft polymerization reaction solution. c. Purification and drying: Add anhydrous ethanol to the graft polymerization reaction solution, the amount of which is twice the volume of the reaction solution. After stirring evenly, let it stand for 30 minutes to allow the copolymer to fully precipitate. Filter and collect the precipitate, wash it three times with anhydrous ethanol to remove unreacted monomers and impurities. Place the washed precipitate in a vacuum drying oven and dry it for 2.5 hours at 65°C and a vacuum of 0.08 MPa. After pulverizing, pass it through an 80-mesh sieve to obtain a chitosan-grafted acrylamide-maleic anhydride copolymer with a grafting rate of 50 wt%. Everything else is exactly the same as in Example 3.
[0068] The cultural paper prepared in Comparative Examples 1-3 was tested, and the test results are shown in Table 3: Table 3 Test data of cultural paper in Comparative Examples 1-3 Surface strength (m / s) 1.95 2.10 1.80 Interlayer bond strength (N / 15mm) 110 125 115 <![CDATA[Bulk (cm 3 / g)]]> 1.82 1.87 1.86 Ash content (wt%) 22.9 21.5 21.0 Flexural endurance (times) 157 162 142 Whiteness (%) 88.5 88.6 88.2 By comparing Comparative Example 1 with Example 3, it can be seen that the surface strength and folding endurance of Comparative Example 1 are significantly lower than those of Example 3. Although the bulk is similar, the physical properties are slightly worse. This comparative example reduced the mass fraction of softwood pulp, which is lower than the critical value of this application. Softwood pulp belongs to the long fiber skeleton and is the main source of paper strength. When its content is too low, it cannot form an effective three-dimensional network support between short fibers, resulting in a loose paper structure and a reduction in fiber bonding points, which directly leads to the paper being very easy to break when subjected to surface tension or repeated folding.
[0069] By comparing Comparative Example 2 with Example 3, it can be seen that the ash content and interlayer bonding strength of Comparative Example 2 are significantly lower. In this comparative example, the amount of chitosan-grafted acrylamide-maleic anhydride copolymer added is only 0.2 parts, indicating that the chitosan-grafted acrylamide-maleic anhydride copolymer plays a relatively key role in the system. It connects the fibers and filler particles through long molecular chains. When the amount added is insufficient, there is a lack of sufficient polymer chains in the system to cover the surface of the fibers and fillers, resulting in a decrease in filler retention rate and a weakening of the bonding force between fibers and fillers, and between fibers, which directly manifests as a decrease in interlayer bonding strength and an inability to form a dense paper structure.
[0070] By comparing Comparative Example 3 with Example 3, it can be seen that the surface strength, folding endurance and ash content of Comparative Example 3 are lower than those of Example 3. This comparative example used a chitosan-grafted acrylamide-maleic anhydride copolymer with a grafting rate of only 50%. The grafting rate determines the number of active sites and spatial configuration of polymer molecules. A grafting rate that is too low means that the polymer chain is too short or there are too few active groups, which cannot form effective anchoring and cross-linking on the surface of fibers and fillers. This results in the chitosan-grafted acrylamide-maleic anhydride copolymer being unable to effectively disperse the filler, leading to filler agglomeration and poor retention, and also failing to play a role in reinforcing the bonding.
[0071] The above are all preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Therefore, all equivalent changes made in accordance with the structure, shape and principle of the present invention should be covered within the scope of protection of the present invention.
Claims
1. A papermaking process for cultural paper, characterized in that, Includes the following steps: Initial pulp preparation: 10-15 parts by weight of bleached sulfate softwood pulp, 15-25 parts by weight of fine fiber waste pulp, and 60-75 parts by weight of poplar mechanical pulp are separately pulped and then mixed evenly to obtain the initial pulp. The preparation method of the fine fiber waste pulp is as follows: Select waste paper of the same type for cultural use, and add 0.2-0.4 wt% of fiber interface activating component. The pulp is then broken down in a hydrauler at a temperature of 25-35℃, followed by high-consistency beating to control the freeness at 45-60°SR, and then purified through an 80-mesh arc sieve to obtain fine fiber waste pulp with a concentration of 10-15 wt%. The fiber interface activating component includes sorbitol, glycerol, and quaternized chitosan oligosaccharide, wherein the mass ratio of sorbitol, glycerol, and quaternized chitosan oligosaccharide is 1.5-3.5:0.8-1.5:
1. Slurry treatment: Add wet-end additives to the initial slurry and mix evenly to obtain papermaking slurry; the wet-end additives, based on the mass fraction of the initial slurry, include 0.3-0.6 parts of chitosan-grafted acrylamide-maleic anhydride copolymer, 0.8-1.2 parts of polyaluminum chloride, 16-20 parts of calcium carbonate, 0.09-0.15 parts of cationic polyacrylamide, and 1.5-2.5 wt% sodium lignosulfonate-modified bentonite; the order of adding the wet-end additives is as follows: add polyaluminum chloride to the initial slurry, stir and disperse for 3-5 minutes, then add calcium carbonate, stir and disperse for 5-7 minutes, then add chitosan-grafted acrylamide-maleic anhydride copolymer, ultrasonically disperse for 4-6 minutes, then add cationic polyacrylamide, stir for 2-4 minutes, and finally add sodium lignosulfonate-modified bentonite, stir and disperse until evenly mixed; The grafting rate of the chitosan-grafted acrylamide-maleic anhydride copolymer was 58–72 wt%. The preparation steps of the sodium lignosulfonate modified bentonite are as follows: calcium-based bentonite is sieved through an 80-mesh sieve, 3-5 wt% sodium lignosulfonate is added to the bentonite, water is added and stirred to obtain a uniform slurry with a solid content of 15-20 wt%. Papermaking and post-processing: The papermaking pulp is diluted with process water, and then processed by wire forming, pressing and dewatering, and drying to produce cultural paper.
2. The papermaking process for cultural paper according to claim 1, characterized in that, The degree of substitution of the quaternary ammonium group in the quaternized chitosan oligosaccharide is 0.1 to 0.
5.
3. The papermaking process for cultural paper according to claim 1, characterized in that, In the papermaking and post-processing steps, the process water includes treated papermaking white water and tap water, wherein the volume ratio of treated papermaking white water to tap water is 0.8 to 1.2:1; the treatment steps of the papermaking white water include: sedimenting and separating the white water generated during papermaking to obtain upper overflow clarified water, wherein 60 to 80 wt% of the upper overflow clarified water is used for pulp dilution, and 20 to 40 wt% of the overflow clarified water is discharged after environmental protection treatment.
4. The papermaking process for cultural paper according to claim 3, characterized in that, In the papermaking and post-processing steps, the precipitation separation method is as follows: Pretreatment: The white water generated from papermaking is first passed into an inclined plate sedimentation tank, and flocculant accounting for 0.06-0.1 wt% of the white water mass is added. The mixture is stirred at 80-120 r / min for 5-8 min. The flocculant includes polyferric sulfate and diatomaceous earth, wherein the mass ratio of polyferric sulfate to diatomaceous earth is 1-3:
1. Filtration: The pretreated white water is filtered through a filter cloth with a pore size of 2-5 μm to obtain filtered white water; Impurity removal: Quaternized polyamide and polyoxyethylene polyoxypropylene ether are added to the filtered white water, wherein the amount of quaternized polyamide and polyoxyethylene polyoxypropylene ether added accounts for 0.03-0.06 wt% and 0.02-0.04 wt% of the mass of the filtered white water, respectively.
5. The papermaking process for cultural paper according to claim 1, characterized in that, In the copying and post-processing steps, the drying method is as follows: first, dry at 80-90℃ for 10-15 minutes; then dry at 110-120℃ for 8-10 minutes; and finally dry at 95-105℃ for 5-8 minutes.
6. The papermaking process for cultural paper according to any one of claims 1-5, characterized in that, In the copying and post-processing steps, an equilibration step is set after the drying process. The equilibration step is as follows: first, it is naturally cooled to below 40°C, and then it is allowed to stand for equilibration for 12 to 15 minutes under the conditions of temperature 25 to 28°C and relative humidity 45 to 55%.
Citation Information
Patent Citations
Preparation method of cultural paper
CN118581764A
Dry expanded paper and manufacturing method thereof
CN118498124A
Paper, method for producing paper and apparatus for producing paper
JP2007177332A